Association of polygenic risk for schizophrenia with fast sleep spindle density depends on pro-cognitive variants - Schilling, Claudia; Zillich, Lea; Schredl, Michael; Frank, Josef; Schwarz, Emanuel; Deuschle, Michael; Meyer-Lindenberg, Andreas; Rietschel, Marcella; Witt, Stephanie; Streit, Fabian (European archives of psychiatry and clinical neuroscience, 2022)
Cognitive impairment is a common feature in schizophrenia and the strongest prognostic factor for long-term outcome. Identifying a trait associated with the genetic background for cognitive outcome in schizophrenia may aid in a deeper understanding of clinical disease subtypes. Fast sleep spindles may represent such a biomarker as they are strongly genetically determined, associated with cognitive functioning and impaired in schizophrenia and unaffected relatives. We measured fast sleep spindle density in 150 healthy adults and investigated its association with a genome-wide polygenic score for schizophrenia (SCZ-PGS). The association between SCZ-PGS and fast spindle density was further characterized by stratifying it to the genetic background of intelligence. SCZ-PGS was positively associated with fast spindle density. This association mainly depended on pro-cognitive genetic variants. Our results strengthen the evidence for a genetic background of spindle abnormalities in schizophrenia. Spindle density might represent an easily accessible marker for a favourable cognitive outcome which should be further investigated in clinical samples.
Gesehen am 04.09.2023